Using Comic Strips Teaching Materials in Group Work to Improve Reading Comprehension of Grade Ninth - Handrianita Mekuo; Luh Gd Rahayu Budiarta (SEAQIL Journal of Language Education, 2023)
A classroom action research (CAR) was conducted to improve the reading comprehension of class IX students of SMP Negeri 1 Latoma in the 2022/2023 academic year by using Comic Strips Teaching Materials in Group Work Activities. The instruments used were questionnaire sheets, student reading scores, and teacher observation sheets. The success indicator is a score of 70. Two cycles were carried out; each consists of four steps: planning, action, observation, and reflection. The first cycle consisted of three meetings including pre-test, material giving, and post-test I. The second cycle consisted of two meetings covering material explanation and post-test 2. Questionnaires are given at the last meeting of each cycle. From the results of the pre-test, it was found that there were only 8% students could pass the success indicator. After being given action in Cycle 1, students who can achieve success indicators are 25%. The number increased in Cycle 2 to 67%. The analysis of the researcher's observation sheet showed a positive response to teaching materials and group work activities. From the questionnaire, it is found that Comic Strips Teaching Materials in Group Work Activities can help students in reading report texts. Therefore, it can be concluded that the use of comic strips teaching materials in group work activities can improve the reading comprehension of grade IX students of SMP Negeri1 Latoma in the 2022/2023 academic year. Similar research can effectively be applied to classrooms in schools with the inadequacy of technology facilities for teaching material procurement.